Studi Pemanfaatan Relai Jarak Quadrilateral untuk Proteksi Saluran Distribusi dengan Pembangkit Tersebar - Adrianti Adrianti; Muhammad Nasir; Muhammad Rivaldi (Jurnal Rekayasa Elektrika, 2020)
Installation of distributed generations (DGs) in distribution network bring benefits for power system operation. However, DGs change the distribution network topologies from radial with one source into multi-sources network, hence magnitude and direction of the current will also change. Consequently, the existing distribution line protection i.e. current based protection, experience performances deterioration. To overcome this problem, distance relays, which work based on calculated impedance is proposed. However, since mho distance relays fail to detect faults through resistance in previous research, quadrilateral characteristic of distance relay is chosen. Quadrilateral distance relays have separate setting for reach and resistance; hence it is expected it will accommodate fault resistance. Therefore, this research aims to identify the performance of quadrilateral distance relay in protecting distribution lines that having DG. The research method is computer simulation where quadrilateral distance relays performance is tested for various faults and system conditions in a test system. The software for the simulation is Digsilent Power factory. The results conclude that the quadrilateral distance relays experienced failures to detect faults in correct zone operation due to a weak source of DG. DG generates less fault current, as consequences, the relays see large impedances.